Preoperative RDW –Albumin Ratio as a Prognostic Biomarker in Gastric Cancer Surgery - Xinhang Cao; Weiwei Shang; Dandan Xiao; Wei Wang; Ziyu Wang; Yangbai Sun; Yan Zhang; Mingzhe Ma (Cancer Medicine, 2026)
ABSTRACT Background The ratio of red blood cell distribution width (RDW) to serum albumin (RAR) combines hematologic and nutritional information from routine blood tests and has shown potential value for prognostication in several diseases. This study aimed to evaluate the prognostic significance of preoperative RAR in patients with gastric cancer undergoing curative gastrectomy and to explore whether RAR could provide additional prognostic information beyond conventional indicators such as TNM stage. Aims This study evaluated the prognostic value of preoperative RAR in patients with gastric cancer undergoing curative resection. Specifically, we aimed to (i) determine the association between RAR and clinicopathological characteristics, (ii) assess its predictive value for overall survival (OS) and disease‐free survival (DFS), and (iii) evaluate the complementary prognostic value of RAR beyond conventional indicators such as TNM stage and other markers. Methods This is a retrospective cohort study including 6988 patients with gastric cancer who underwent curative resection at a tertiary cancer center between July 2011 and December 2022. We explored associations between preoperative RAR and a range of clinicopathological characteristics. Overall survival was estimated by the Kaplan–Meier method, and Cox proportional hazards models were used to assess factors influencing prognosis. The discriminative ability of RAR was evaluated using time‐dependent ROC analysis. Results An elevated baseline RAR was associated with older age, larger tumor dimensions, higher TNM classification, lymphatic spread, deeper tumor invasion, and the presence of vascular and perineural invasion, with poorer overall survival (OS) and disease‐free survival (DFS). Time‐dependent receiver operating characteristic analyses indicated that RAR consistently achieved higher discriminative performance than neutrophil‐to‐lymphocyte ratio (NLR), lymphocyte‐to‐monocyte ratio (LMR), and platelet‐to‐lymphocyte ratio (PLR) across follow‐up. However, the absolute AUC values remained modest, indicating that RAR alone has limited predictive capacity. Conclusion RAR may facilitate postoperative risk stratification as an accessible prognostic marker.